2019
DOI: 10.1371/journal.pone.0217668
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for predicting protein epitopes targeted by antibody repertoires using whole proteomes

Abstract: Antibodies are essential to functional immunity, yet the epitopes targeted by antibody repertoires remain largely uncharacterized. To aid in characterization, we developed a generalizable strategy to predict antibody-binding epitopes within individual proteins and entire proteomes. Specifically, we selected antibody-binding peptides for 273 distinct sera out of a random library and identified the peptides using next-generation sequencing. To predict antibody-binding epitopes and the antigens from which these e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…However, these platforms could not provide epitope information at amino acid level, and pathogen specific protein or peptide library need to be constructed individually, which is costly and time-consuming. Alternatively, random peptide libraries were attempted for dissecting pathogen specific IgG responses from sera ( 34, 35 ). For SARS-CoV-2, following the protocol of testing serum directly that we established ( 34 ), and the K-TOPE algorithm ( 35 ), we tried to profile the virus specific IgG responses at proteome level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these platforms could not provide epitope information at amino acid level, and pathogen specific protein or peptide library need to be constructed individually, which is costly and time-consuming. Alternatively, random peptide libraries were attempted for dissecting pathogen specific IgG responses from sera ( 34, 35 ). For SARS-CoV-2, following the protocol of testing serum directly that we established ( 34 ), and the K-TOPE algorithm ( 35 ), we tried to profile the virus specific IgG responses at proteome level.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, random peptide libraries were attempted for dissecting pathogen specific IgG responses from sera ( 34, 35 ). For SARS-CoV-2, following the protocol of testing serum directly that we established ( 34 ), and the K-TOPE algorithm ( 35 ), we tried to profile the virus specific IgG responses at proteome level. However, most of the identified epitopes that match the sequence of SARS-CoV-2 proteins are of low frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing data from each sample was processed to generate a non-redundant peptide list of antibody binding epitopes using publicly available software as described 30 . FASTQ DNA sequencing files were deposited into the NCBI Sequence Read Archive (SRA) for public access.…”
Section: Generation Of Antibody Epitope Repertoiresmentioning
confidence: 99%
“…burgdorderi immune response. Given that most of the binding energy is typically derived from 4-6 amino acids [17], the specificity of antigen-antibody interaction is defined by only a few anchor residues within an epitope [29, [96][97][98]. Previoulsy, we [27] and others [34] demonstrated that the four-amino-acid consensus is a minimum motif length, which is sufficient to define an antibody specificity.…”
Section: Fig 5 Clustvis-generated Principal Component Analysis Plotsmentioning
confidence: 99%